Analisis Hukum Keselamatan Penerbangan dalam Interaksi Pesawat Udara Komersial dan Pesawat Udara Negara di Bandar Udara Studi Kasus Accident JAL516 dan JA7222A di Bandar Udara Haneda, Tokyo, Jepang - Wazier, Ronny; Sujono, Sujono; Sudarto, Sudarto (Neolectura, 2025)
Aviation safety law regulates the interaction between commercial aircraft and state aircraft, particularly in relation to airspace management and conflict avoidance at airports. The case studies of the JAL516 and JA7222A Accidents at Haneda Airport, Tokyo, Japan illustrate how regulatory violations and lack of coordination between civil and military authorities can pose serious safety risks. In both incidents, commercial aircraft were involved in events that threatened the safety of passengers and crew due to the lack of data transparency and communication between the civil and military sectors. These cases demonstrate the need for the implementation of Flexible Use of Airspace (FUA) to efficiently divide airspace, as well as the use of Collaborative Decision Making (CDM) to ensure effective coordination between stakeholders. The adoption of modern technologies, such as artificial intelligence (AI)-based air traffic management systems, can help identify potential conflicts earlier and provide solutions in real time. In this context, air law must continue to adapt to ensure the protection of civil aviation, prioritizing transparency, increasing international cooperation, and implementing stronger regulations to prevent similar accidents in the future.